Gestão ambiental portuária maranhense: análise do gerenciamento do risco de derrame de óleo no Complexo Portuário de São Luís - MATOS, Diego Lima (2018)
Among the various environmental aspects related to maritime transport and port logistics of petroleum-derived fuels is one that, although not routine, can cause serious environmental impacts, which is the risk of oil spillage into water bodies. Given that, at least in the short term, as there is no possibility of withdrawing this source of non- renewable energy from fossil fuels, because this source is one of the main engines of the current economy, the need arises to manage this risk. Thus, the present work aims to diagnose and analyze the situation of the oil spill risk management systems of the companies that operate in the Port Complex of São Luís (CPSL). As a source of data collection for the research, we used newspaper reports and reports of incidents involving oil spills in the last 30 years (1987-2017), current data from the sustainability reports and the Environmental Performance Index (IDA) as well as the main accidental hypotheses and a proposal for a structure of material resources to respond to incidents included in the Individual Emergency Plans (PEI) of companies in the CPSL region, as well as the collection of information from the application of the form to the environmental managers of the ports of the CPSL. As a result, it was found that most of the origins of the cases found in both news and in the PEIs are from ships and pipelines, while the loads of leaks were considered by the news to be largely small, whereas in the case of PEI, there was a predominance of large volume scenarios. Regarding the number of occurrences contained in sustainability reports, almost no mention was made of them, while, on the other hand, the managers' concern about highlighting the use of risk management as part of the organization's strategy was identified. Both occurrences and risk management systems have had similar results when obtained from the IDA for companies in the region. As for the port managers' forms, they also show a certain uniformity in meeting the minimum management system requirements, environmental auditing and main sources of risk. Regarding the material resources to respond to oil incidents in ports, most of these main elements meet the requirements of PEIs.